Early complication of a subtrochanteric periprosthetic fracture following hip resurfacing. Is varus healing acceptable? A case report and literature review. - Lugani, Giovanni; Santandrea, Alessandro; Puddu, Leonardo; Rigoni, Massimo; Cont, Fabrizio; Magnan, Bruno; Cortese, Fabrizio (Acta Biomedica Atenei Parmensis, 2021)
Background: The increase in the incidence of osteoarthritis of the hip (coxarthrosis) in young patients with high functionality requirements and the development of new materials in the last twenty years have resulted in an increase in the number of surgeries involving hip resurfacing procedures. There has also been an increase in associated periprosthetic fractures, which currently occur in 1%-2% of cases. According to the medical literature, fractures of this type can be treated conservatively, using reduction and synthesis or through prosthetic revision. Case report: Patient aged 69 years who had undergone resurfacing of the right hip ten years previously, who came to our attention as a result of direct contusion trauma with x-ray evidence of a periprosthetic fracture in the subtrochanteric region. We treated the fracture by preserving the prosthesis and performing osteosynthesis using a plate and screws. After two months the synthesis was complicated by breakage of a proximal screw and varus collapse of the fracture. We treated this complication conservatively by adjusting the weight-bearing regime and administering physical and drug therapy. Six months after the fracture, despite the residual varus displacement and the less than stellar x-ray result, the clinical outcome was satisfactory. Discussion and conclusions: Treatment of periprosthetic fractures following hip resurfacing is often technically complex. The major difficulties arise from the presence of prosthetic components and the limited bone stock available. Fractures often affect the neck of the femur and the trochanteric region, and in rare cases there is involvement of the subtrochanteric region. Our review confirms this trend and raises the question as to which method of synthesis is ideal for a fracture pattern so rarely described in the literature.